Critically Ill Patients with Coronavirus Disease 2019 in a Designated ICU: Clinical Features and Predictors for Mortality - Wang ZH; Shu C; Ran X; Xie CH; Zhang L (Dove Medical Press, 2020)
Zhao-Hua Wang,1,* Chang Shu,2,* Xiao Ran,1 Cui-Hong Xie,1 Lei Zhang2 1Department of Critical Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 2Department of Surgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei ZhangDepartment of Surgery, Tongji Hospital, 1095 Jiefang Avenue, Wuhan 430030, People’s Republic of ChinaTel +86-27-83665312Email zhangl@tjh.tjmu.edu.cnBackground: Coronavirus disease 2019 (COVID-19) is a worldwide pandemic outbreak with a high mortality. Prognostic factors of critically ill patients with COVID-19 have not been fully elucidated yet.Methods: In the present study, 59 patients with COVID-19 from the intensive care unit of the Caidian Branch of Tongji Hospital were enrolled. Epidemiological, demographic, clinical, laboratory, radiological, treatment data, and clinical outcomes were collected. Prognostic factors were statistically defined.Results: Of the 59 patients studied (67.4± 11.3 years), 38 patients were male, 51 had underlying diseases, and 41 patients died during admission. Compared with the survivors, the deceased patients were of older age, had more smoking history, severer fatigue, and diarrhea, a higher incidence of multiple organ injuries, more deteriorative lymphopenia and thrombocytopenia, remarkably impaired cellular immune response, and strengthened cytokine release. Age higher than 70 (OR=2.76, 95% CI=1.45– 5.23), arrhythmia (OR=4.76, 95% CI=1.59– 14.25), and a Sequential Organ Failure Assessment (SOFA) score above 4 (OR=5.16, 95% CI=1.29– 20.55) were identified as risk factors for mortality of patients.Conclusion: Critically ill COVID-19 patients aged higher than 70, arrhythmia, or a SOFA score above 4 have a high risk of mortality, and need prior medical intervention.Keywords: severe acute respiratory coronavirus 2, pneumonia, critically ill, mortality, prognostic factor